Eksperimentasi Strategi Pembelajaran Inkuiri Terbimbing dan Kooperatif Tipe Student Teams Achievement Divisions (STAD) terhadap Konsep Diri Siswa ditinjau dari Kreativitas Belajar Fisika Pada Siswa Kelas X MAN 2 Sragen - Sunarjo, Sunarjo, Dr. Sumardi, M.Si, Dr. Sabar Narimo, M.M., M.Pd (2016)
ABSTRACT SUNARJO, Q100140027. EXPERIMENTATION GUIDED INQUIRY STRATEGY AND COOPERATIVE LEARNING TYPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) OF STUDENTS SELF-CONCEPT BASED ON CREATIVITY IN LEARNING PHYSICS IN CLASS X MAN 2 SRAGEN. THESIS. MUHAMMADIYAH SURAKARTA UNIVERSITY. 2016. The aim of this study was as follows. (1) Examine the difference in the effect of the use of learning strategies guided inquiry and cooperative STAD to the self concept of students. (2) Examine the difference in the effect of creativity in learning physics students who have high creativity, middle creativity and low creativity to student self-concept. (3) Examine the interaction between the use of learning strategies with self-concept of students in relation to creativity in learning physics. This research is a quasi experimental research design using 2 X 3 factorial design. Study population was all students of class X MIPA at MAN 2 Sragen in 2015/2016. The sample in this research is class X MIPA1 consist of 40 students as an experimental class and class X MIPA2 consist of 40 students as the control class is taken by cluster random sampling were then carried out tests of balance flats with t test. Data collection techniques used are questionnaires and documentation. Data analysis technique used are two-ways analysis of variance with different cell sizes and further test with Scheffe method were previously performed tests of normality and homogeneity test. From the analysis of variance of two roads with a cell is not the same at significance level = 0.05 indicates ( 1 ) There is a significant effect strategy guided inquiry and cooperative learning STAD type of self-concept of students in the subjects of physics static fluid material (Fhit. = 13,340 > 3,96 = Ftabel). ( 2 ) There is influence signifnifikan between the creativity of self-concept study physics student at the static fluid material (Fhit. = 73,069 > 3,11 = Ftabel) . ( 3) There was a significant interaction between the learning strategy , learning creativity physics of the self-concept of the student ( Fhit. = 4,861 > 3,11 = Ftabel). Keywords: guided inquiry, self-concept, STAD-cooperatif, creativity